As tecnologias digitais de informação e comunicação (TDIC’S) no contexto de ensino da matemática: aplicação de vídeos de animações no estudo de matrizes - VILHENA, Patrício de Jesus Quaresma de (2019)
In the development of the theme "Digital Information and Communication Technologies (TDIC's) in the context of Mathematics teaching: application of animation videos in Matrix study", the present work contributes to the fact that the methodologies developed in the classroom, when they present new ways of approaching mathematics, sharpen students' curiosity and interest, especially in mathematics, which is labeled as a difficult discipline to understand and out of reality. Thus, offering practical grants for teachers to develop the teaching of mathematics satisfactorily, from the animation videos tool, is the main focus of the work. In order to reach this proposal, a bibliographical review of the main authors dealing with the issue of teaching in mathematics using information and communication technologies (TDIC's) was carried out. After this approach was carried out a workshop directed to the students of the Cristo Trabalhador College, in the class of the second year of high school, where lecture was given with the aforementioned resource. After the workshop, questionnaires were applied to the students and to the class teacher about the teaching of Mathematics, specifically matrices, with animation videos, indicating the possibility of their use in the classroom with their students and characterizing an auxiliary tool in teaching.